Systematic Literature Review On Information Technology (IT) Skills And Understanding For Internal Auditors - Harahap, Aulia Rahman (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This systematic literature review examines the evolving role of Information Technology (IT) skills and understanding in enhancing the effectiveness of internal auditors. In recent years, the growing complexity and reliance on digital systems in organizations have prompted a shift in the required skill set for internal auditors. The review synthesizes studies from diverse sources to identify key IT competencies, tools, and frameworks that contribute to the internal audit function. It explores how IT knowledge influences auditing processes, risk management, and compliance assurance. Through a rigorous selection of peer-reviewed articles, books, and case studies, the review highlights the increasing importance of IT skills, including data analytics, cybersecurity awareness, and knowledge of emerging technologies. The findings indicate that internal auditors who possess a robust understanding of IT systems are better equipped to identify risks, evaluate controls, and provide strategic insights. The review also discusses the challenges auditors face in acquiring and applying these skills and offers recommendations for continuous professional development. Ultimately, this review underscores the necessity for internal auditors to bridge the gap between traditional auditing practices and modern technological advancements to enhance organizational governance and performance.